The Role of Social Media Narratives in Shaping Consumer Trust and Brand Loyalty : A Literature Review - Arni Nuraeni; Salsabila (Trasearch (Training, Research and Academy Society, 2025)
In an era increasingly defined by digital communication, social media has emerged as a dominant platform for brand storytelling and consumer engagement. However, the mechanisms by which social media narratives influence consumer trust and brand loyalty remain fragmented and under-theorized in current literature. This study aims to explore the role of social media narratives in shaping trust-based consumer-brand relationships and fostering long-term brand loyalty. Employing a qualitative literature review approach, the study synthesizes findings from over 40 peer-reviewed articles and academic sources published between 2018 and 2024. Thematic analysis reveals that authenticity, emotional resonance, and cultural alignment are the most influential narrative elements that shape consumer perceptions and drive brand commitment. Moreover, narratives that are co-created with consumers and embedded in community values demonstrate a stronger effect on fostering relational trust. The study also uncovers theoretical gaps in the integration of narrative theory with digital consumer behavior frameworks. Practical implications suggest that brands must move beyond transactional communication and invest in consistent, humanized storytelling to strengthen consumer relationships. The review offers a foundation for future empirical research and provides strategic insights for marketers seeking to build trust and loyalty in the ever-evolving digital ecosystem.